2020
DOI: 10.1038/s41598-020-74528-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of removal and adsorption enhancement of high-flux hemodialyzers in convective therapies by a novel in vitro uremic matrix

Abstract: Adsorption properties of hemodialyzers are traditionally retrieved from diffusive treatments and mainly focused on inflammatory markers and plasma proteins. The possible depurative enhancement of middle and high molecular weight solutes, as well as protein-bound uremic toxins by adsorption in convective treatments, is not yet reported. We used discarded plasma exchanges from uremic patients and out-of-date erythrocytes as a novel in vitro uremic precursor matrix to assess removal and adsorption patterns of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Several studies have previously demonstrated the efficient removal of other PBUTs such as furancarboxylic acid and pentosidine [46,47], as well as inflammatory markers such as TNF-α, IL-1β, IL-6, and C-reactive protein, by other PMMA dialyzers [48]. The high protein adsorption capacity of these membranes is due to their symmetrical pore structure which provides a large specific surface area [28,49]. Whereas in PMMA membranes the whole membrane thickness is involved in the separation process allowing toxin adsorption, in PS membranes (with asymmetrical pores) only a fine layer of ≈1 µm is responsible for the separation process, while the remaining membrane thickness has structural functions only [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have previously demonstrated the efficient removal of other PBUTs such as furancarboxylic acid and pentosidine [46,47], as well as inflammatory markers such as TNF-α, IL-1β, IL-6, and C-reactive protein, by other PMMA dialyzers [48]. The high protein adsorption capacity of these membranes is due to their symmetrical pore structure which provides a large specific surface area [28,49]. Whereas in PMMA membranes the whole membrane thickness is involved in the separation process allowing toxin adsorption, in PS membranes (with asymmetrical pores) only a fine layer of ≈1 µm is responsible for the separation process, while the remaining membrane thickness has structural functions only [20].…”
Section: Discussionmentioning
confidence: 99%
“…Technical characteristics of the dialyzers. Adapted from Cavalier, 2017; Masakane, 2017; and Gómez, 2020[25,27,28].…”
mentioning
confidence: 99%
“…Once the patient was disconnected, an elution protocol presented elsewhere [18] was implemented. The obtained eluate ( V eluate ∼ 160–250 mL) was collected into 50 mL propylene tubes and stored at −80°C until processing.…”
Section: Methodsmentioning
confidence: 99%
“…Results of such experimental studies have been reported using modules after in vitro tests (e.g. [ 22 ]); however, very few test results are available with “fouled” HC filters after a session (e.g. [ 23 ]), as outlined below.…”
Section: Albumin Losses During Haemocatharsismentioning
confidence: 99%